A prospective randomised trial of a "test and treat" policy versus endoscopy based management in youngHelicobacter pylori positive patients with ulcer-like dyspepsia, referred to a hospital clinic. (1st August 1999) - Heaney, A; Collins, J S A; Watson, R G P; McFarland, R J; Bamford, K B; Tham, T C K
Abstract : BACKGROUND: Management of dyspepsia remains a controversial area. Although the European Helicobacter pylori study group has advised empirical eradication therapy without oesophagogastroduodenoscopy (OGD) in young H pylori positive dyspeptic patients who do not exhibit alarm symptoms, this strategy has not been subjected to clinical trial. AIMS: To compare a "test and treat" eradication policy against management by OGD. PATIENTS: Consecutive subjects were prospectively recruited from open access OGD and outpatient referrals. METHODS: H pylori status was assessed using the carbon-13 urea breath test. H pylori positive patients were randomised to either empirical eradication or OGD. Symptoms and quality of life scores were assessed at baseline and subsequent reviews over a 12 month period. RESULTS: A total of 104 H pylori positive patients aged under 45 years were recruited. Fifty two were randomised to receive empirical eradication therapy and 52 to OGD. Results were analysed using an intention to treat policy. Dyspepsia scores significantly improved in both groups over 12 months compared with baseline; however, dyspepsia scores were significantly better in the empirical eradication group. Quality of life showed significant improvements in both groups at 12 months; however, physical role functioning was significantly improved in the empirical eradication group. Fourteen (27%) in the empirical eradication group subsequently proceeded to OGD because of no improvement in dyspepsia. CONCLUSIONS: This randomised study strongly supports the use of empirical H pylori eradication in patients referred to secondary practice; it is estimated that 73% of OGDs in this group would have been avoided with no detriment to clinical outcome.